PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA DIVISI HOUSEKEEPING PT AEON DELIGHT INDONESIA JAKARTA SELATAN - Bellaika Kurdyana; Ana Septia Rahman (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine how much influence leadership style and work motivation have on employee performance at the Housekeeping Division of PT Aeon Delight Indonesia South Jakarta both partially and simultaneously. The type of research used in this study is quantitative research with a descriptive approach. The sample obtained by the author in this study used the slovin formula, which is the formula used to find the sample size that is considered capable of representing the entire population. The sample used by the authors in this study amounted to 60 respondents. The data collection method used in this research is primary data. The primary data taken is the results of the questionnaire. The results showed that Leadership Style has a positive and significant influence on Employee Performance where the t value is obtained> t table or 7.095> 2.001 and reinforced by the ρ value < Sig.0.05 or 0.000 < 0.05. Work Motivation has a positive and significant influence on Employee Performance where the t value is obtained> t table or 9.999> 2.001. and strengthened by the ρ value < Sig.0.05 or 0.000 < 0.05. Leadership Style and Work Motivation have a positive and significant influence on Employee Performance where the calculated F value> F table or 53.840> 3.16 is obtained, this is also reinforced by the ρ value < Sig.0.05 or 0.000 < 0.05.